A solubilidade do magnésio do calcário dolomítico no solo: II. ensaio em vasos com fumo - Mello, Francisco A.F. de; Arzolla, Sylvio (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
The authors present the results of an experiment carried out in pots in order to study the efficiency of dolomitic limestone as a magnesium fertilizer for tobacco (Nicotiana tabacum L., var. Goiano). They concluded by foliar analysis that under the experimental conditions of the test dolomitic limestone was as good source of Mg as MgSO4.